Design, characterization and management of a wireless sensor network for smart gas monitoring - Jelicic, V.; Magno, M.; Paci, G.; Brunelli, D.; Benini, L. (2011 4th IEEE International Workshop on Advances in Sensors and Interfaces, 2011)
Air quality monitoring in indoor environments is of great significance for comfort and health, especially nowadays that people spend more than 80% of the day indoor. We propose a flexible wireless system able to detect polluted air and dangerous situations in a complex and large environment. It is important for ambient intelligent systems to be unobtrusive and to optimize the power consumption of the platforms in order to be able to live on batteries for several years. We present a system with aggressive energy management that involves three levels: sensor level, node level and network level. The sensor board we designed is a wireless sensor network (WSN) node, with very low sleep current consumption (only 8 μA). It contains two modalities - a gas sensor and a Pyroelectric InfraRed (PIR) sensor. The network is multimodal: it uses information from the PIR sensor and neighbor nodes to detect the presence of people and to modulate the duty cycle of the node and the Metal Oxide Semiconductor (MOX) gas sensor. In this way we reduce the nodes' activity and energy requirements, providing a reliable service at the same time. We simulate the benefits of the context-aware adaptive duty-cycling of the gas sensor activity and we demonstrate a significant lifetime extension compared to the continuously driven gas sensor (several years vs. several days).